Analysis of Electronic Teaching Materials Validity from Research Result Product of Student’s Thesis Development at Mathematics Education Department of State Islamic University Sultan Syarif Kasim Riau (Tarbiyah Suska Conference Series, 2022)
The purpose of this research is to find out how the validity of electronic teaching materials from a result of research thesis product development at Riau Mathematics Education students. The subject of the research is the students who had the results of development research in the form of electronic teaching materials in 2021 and 2022. The type of this research is qualitative research, with descriptive methods. The design of the research is a case study, with data collection techniques, namely documentation and interviews. The results of data analysis not only to show that students who develop electronic teaching materials need a lot of time to be proficient in producing electronic teaching materials, but also the students who are greatly facilitated by Youtube videos in order to learn how to make electronic teaching materials such as e-modules using Flip PDF Professional and e-LKS by using liveworksheets. From a technical point of view in the electronic field, students have the potential to produce electronic teaching materials that are very useful for learning mathematics in recent day. It is in line with the demands that an educator must be able to keep up with technological developments so that the learning process runs as needed. However, when it is viewed from the composition of the material and learning activities, it has not shown an important message from the concept of the mathematical material itself, and the resulting arrangement tends to only use formulas as a starting pointb to place the concepts to the students by using practice questions, students are rarely directed based on their experience and basic knowledge, as a result the learning process tends to be not meaningful for students. Based on the results of the general analysis, it is necessary to hold a material validation team that is totally facilitated so that the results of the validity test of student development products are truly tested and ready to use, then in the future the results of research products for developing student thesis for Mathematics Education at UIN Suska Riau are suitable for its sustainable use and it is ready to be marketed.